2018
DOI: 10.1101/330688
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Activity-dependent netrin-1 secretion drives synaptic insertion of GluA1-containing AMPA receptors in the hippocampus

Abstract: Dynamic trafficking of a-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid glutamate receptors (AMPARs) to synapses is critical for activity-dependent synaptic plasticity underlying learning and memory, however the identity of key molecular effectors remains elusive. Here, we demonstrate that membrane depolarization and N-methyl-D-aspartate receptor (NMDAR) activation triggers secretion of the chemotropic guidance cue netrin-1 from dendrites. Using selective genetic deletion, we show that netrin-1 expression … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
76
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(80 citation statements)
references
References 82 publications
3
76
0
1
Order By: Relevance
“…Further, application of exogenous netrin-1 is sufficient to trigger insertion of GluA1-containing a-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid glutamate receptors (AMPARs). Together, these findings indicate that netrin-1 participates in activity-dependent plasticity at Schaffer-collateral synapses, that netrin-1 is secreted by neurons in response to activity, and that netrin-1 is sufficient to evoke lasting synaptic potentiation (Glasgow et al 2018). Here we report that conditional deletion of netrin-1 from principal excitatory neurons results in deficits in hippocampal-dependent spatial memory, demonstrating that netrin-1 critically regulates memory processes underlying spatial cognition.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Further, application of exogenous netrin-1 is sufficient to trigger insertion of GluA1-containing a-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid glutamate receptors (AMPARs). Together, these findings indicate that netrin-1 participates in activity-dependent plasticity at Schaffer-collateral synapses, that netrin-1 is secreted by neurons in response to activity, and that netrin-1 is sufficient to evoke lasting synaptic potentiation (Glasgow et al 2018). Here we report that conditional deletion of netrin-1 from principal excitatory neurons results in deficits in hippocampal-dependent spatial memory, demonstrating that netrin-1 critically regulates memory processes underlying spatial cognition.…”
Section: Introductionmentioning
confidence: 88%
“…We have recently reported that neuronal expression of netrin-1 in principal excitatory neurons impairs long-term potentiation in the adult hippocampus, suggesting that netrin-1 may be necessary for spatial memory formation (Glasgow et al 2018). To test the hypothesis that netrin-1 made by glutamatergic neurons in the forebrain contributes to memory formation, we tested CaMKII-Cre/NTN1 f/f (NTN1 cKO) and wild-type age-matched littermate controls in the hippocampus-dependent Morris water maze (MWM) task (Morris et al 1982).…”
Section: Selective Deletion Of Netrin-1 From Forebrain Glutamatergic mentioning
confidence: 99%
See 1 more Smart Citation
“…17 DCC regulates synaptic function including NMDA receptordependent synaptic plasticity in maturated brains. 18,19 Anti-DCC autoantibodies are associated more with thymoma and myasthenia gravis and less with LE. 8,20 In 1 human study, however, 4 of 12 patients with DCC antibodies were diagnosed as LE although F I G U R E 4 The case cat serum antibodies do not bind to leucinerich glioma inactivated 1 (LGI1).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggested DCC and netrin-1 contribution to synaptic excitation. 18,19 Therefore, the possibility of direct contribution of DCC antibodies to the pathogenesis of LE should be considered in the future.…”
Section: Discussionmentioning
confidence: 99%